دراسة تركيز الكلور الحر المتبقي في شبكة مياه الشرب (حالة دراسة: حي الرمل الشمالي – مدينة اللاذقية) - عليا, تميم (Latakia University Journal -Engineering Sciences Series, 2019)
تعتبر مسألة تطهير المياه إحدى أهم الإجراءات الهادفة إلى حماية الصحة العامة، إضافةً إلى ذلك فإن المطهرات التي يكون الكلور أساسياً فيها هي المطهرات التي تمتلك خواص البقاء إلى ما بعد عملية التطهير بذلك تقدم حماية مؤكدة و مستمرة للمياه بدءاً من محطة التصفية وصولاً إلى المستهلك النهائي. يرتكز البحث على دراسة جزء من شبكة توزيع المياه في مدينة اللاذقية وذلك بهدف التحقق من عوامل سلامة المياه. لقد اعتمدت الدراسة بشكل أساسي على قياس الكلور المتبقي في شبكة مياه الشرب في حي الرمل الشمالي في مدينة اللاذقية. تم إجراء تحاليل لتحديد نسبة الكلور المتبقي في المكان ليصار فيما بعد إلى توقيع أماكن الاعتيان وقيم الكلور المتبقي فيها على مخطط شبكة توزيع المياه للحي المدروس. لقد أظهرت معظم قياسات الكلور المتبقي تركيزاً أعلى من القيم المسموحة وفق المعايير القياسية السورية لمياه الشرب باستثناء بعض النقاط التي كان فيها تركيز الكلور الحر المتبقي ضمن الحدود المسموحة. لقد تمت مناقشة النتائج التي تم التوصل إليها ووضعت الإيضاحات والمقترحات الهادفة إلى الحفاظ على سلامة ونوعية مياه الشرب. Drinking water chlorination is one of the most significant advances in public health protection. Besides, chlorine-based disinfectants are the only major disinfectants with the lasting residual properties that prevent microbial regrowth and provide continual protection throughout distribution system from the treatment plant to the tap. The research is based on a field study of one part of the distribution system in the municipality of Lattakia to ensure the safety of drinking water. Basically, the study depends on residual free chlorine (RFC) measurements of drinking water distribution system in a selected quarter in Lattakia. The procedures involve a test the RFC in- situ and putting the values on the scheme of distribution system of the mentioned quarters. Generally, the measured values of RFC are higher than maximum permitted level, which is provided by Syrian standard of drinking water, except at some points which had normal concentration of RFC. An explanation of all critical cases is given and recommendations are provided to conserve the drinking water quality and safety.